APLIKASI UNSUR VISUAL BENTUK DAN WARNA MOTIF KAIN TRADISIONAL INDONESIA TIMUR PADA PERANCANGAN FURNITUR MODERN - I WAYAN YOGIK ADNYANA PUTRA; PUTU SURYA TRIANA DEWI (Universitas Mahasaraswati K. Mataram, 2023)
Indonesia is rich in a diversity of cultural crafts, one of which is traditional fabrics that are spread throughout the Indonesian archipelago. The traditional cloth has a spiritual and translingual dimension, which shows the very high level of Indonesian culture. These fabrics are full of symbolic meanings as well as spiritual values contained in the motifs inside. These motifs present various decorative patterns such as geometric, human, animal, plant, natural objects, technological objects, and calligraphy. The purpose of this study is to classify cloth motifs from Eastern Indonesia, which are sacred motifs and which can be explored further. The purpose of this research is to provide an educational basis when these motifs are innovated and applied to a product such as furniture. This study uses a descriptive qualitative analysis method through literature exploration and interviews with craftsmen or community activists for the preservation of Indonesian fabrics. From the research results, it was obtained twenty-four motifs that could be explored and ten motifs that were switchable so that they could not be explored. For motifs that can be explored, it is continued by making a sampling of one of the motifs using the laser cutting method which can then be applied to space elements, one of which is furniture.